North American Big Brown Bats (Eptesicus fuscus) Harbor an Exogenous Deltaretrovirus - Ben M. Hause (American Society for Microbiology, 2020)
ABSTRACT Bats are the reservoir for a large number of zoonotic viruses, including members of Coronaviridae (severe acute respiratory syndrome coronavirus [SARS-CoV] and SARS-CoV-2), Paramyxoviridae (Hendra and Nipah viruses), Rhabdoviridae (rabies virus), and Filoviridae (Ebola virus) as exemplars. Many retroviruses, such as human immunodeficiency virus, are similarly zoonotic; however, only infectious exogenous gammaretroviruses have recently been identified in bats. Here, viral metagenomic sequencing of samples from bats submitted for rabies virus testing, largely due to human exposure, identified a novel, highly divergent exogenous Deltaretrovirus from a big brown bat (Eptesicus fuscus) in South Dakota. The virus sequence, corresponding to Eptesicus fuscus deltaretrovirus (EfDRV), comprised a nearly complete coding region comprised of canonical 5′-gag-pro-pol-env-3′ genes with 37% to 51% identity to human T-lymphotropic virus (HTLV), an infectious retrovirus that causes T-cell lymphoma. A putative tax gene with 27% identity to HTLV was located downstream of the pol gene along with a gene harbored in an alternative reading frame which possessed a conserved domain for an Epstein-Barr virus nuclear antigen involved in gene transactivation, suggesting a regulatory function similar to that of the deltaretrovirus rex gene. A TaqMan reverse transcriptase PCR (RT-PCR) targeting the pol gene identified 4/60 (6.7%) bats as positive for EfDRV, which, combined with a search of the E. fuscus genome that failed to identify sequences with homology to EfDRV, suggests that EfDRV is an infectious exogenous virus. As all known members of Deltaretrovirus can cause malignancies and E. fuscus is widely distributed in the Americas, often with a colonial roosting behavior in human dwellings, further studies are needed to investigate potential zoonosis. IMPORTANCE Bats host a large numbers of viruses, many of which are zoonotic. In the United States, the big brown bat (Eptesicus fuscus) is widely distributed and lives in small colonies that roost in cavities, often in human dwellings, leading to frequent human interaction. Viral metagenomic sequencing of samples from an E. fuscus bat submitted for rabies testing identified the first exogenous bat Deltaretrovirus. The E. fuscus deltaretrovirus (EfDRV) genome consists of the typical deltaretrovial 5′-gag-pro-pol-env-3′ genes along with genes encoding two putative transcriptional transactivator proteins distantly related to the Tax protein of human T-cell lymphotrophic virus and nuclear antigen 3B of Epstein-Barr virus. Searches of the E. fuscus genome sequence failed to identify endogenous EfDRV. RT-PCR targeting the EfDRV pol gene identified 4/60 (6.7%) bats with positive results. Together, these results suggest that EfDRV is exogenous. As all members of Deltaretrovirus are associated with T- and B-cell malignancies or neurologic disease, further studies on possible zoonosis are warranted.